The organizational and human dimensions of successful mentoring programs and relationships - Kochan, Frances K. (Perspectives in mentoring., 2002)
Mentoring has become an important aspect of professional development in a wide variety of fields such as education engineering and business. There is an increased interest in the topic on a global scale. Research indicates that those who receive mentoring rise faster in their organizations and have more success in their careers than those who do have this experience. This series will focus on various aspects of the mentoring process. This book examines mentoring with a focus on enhancing opporutnities for those traditionally ignored in the mentoring process. It includes chapters about mentoring in a variety of settings with varied populations to capture the essence of the experience. The editor gleans the chapters to present an analysis of the organizational factors which should be considered when designing a mentoring program and the human side of the mentoring process. The book should be of interest to those who want to foster the success of others through organizational mentoring intitiatives as well as to individuals who wish to partiicpate in mentoring endeavors as a mentor or mentee.